RENEWABLE ENERGY FOR NORTH-WEST CROATIA - Domac, Julije; Djukic, Sanda (Journal of Energy Technology, 2024)
NorthͲwest Croatia Regional Energy Agency has been founded in 2007 by Zagreb County, Karlovac County, KrapinaͲZagorje County and City of Zagreb under the framework of the Intelligent Energy Europe programme. The main objective and role of the Agency are promoting and encouraging of regional sustainable development in the fields of energy and environmental protection through renewable energy sources (RES) utilization and energy efficiency measures implementation. The Agency provides information and advice to cities and municipalities and a number of other services based on specific local energy needs. This paper describes main activities and results of the Agency. Specific project activities are described in area of strategic documents and support, sustainable energy management in cities, renewable energy promotion, international cooperation and other activities. Carrying out all described and many already planned sustainable energy projects, the Agency will succesfully support its counties, cities and municipalities in making use of energy in this region sustainable and efficient.